Incidental Bystander or Essential Culprit: A Systematic Review of Bacterial Significance in the Pathogenesis of Breast Implant-Associated Anaplastic Large Cell Lymphoma - Foppiani, Jose A; Raska, Otakar; Taritsa, Iulianna; Hernandez Alvarez, Angelica; Lee, Daniela; Escobar-Domingo, Maria J; Berger, Josephine; Klener, Pavel; Schuster, Kirsten A; Abdo, Daoud; Clemens, Mark W; Lin, Samuel J (International journal of molecular sciences, 2023)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a distinct subtype of T-cell non-Hodgkin lymphoma that arises in the context of prolonged exposure to textured breast implants. The intent of this manuscript is to explore whether the bacterial presence in biofilms on these implants is a mere incidental finding or plays a pivotal role in the pathogenesis of BIA-ALCL. Our goal is to delineate the extent of bacterial involvement, offering insights into potential underlying mechanisms, and establishing future research priorities aimed at resolving the remaining uncertainties surrounding this complex association. A comprehensive systematic review of several databases was performed. The search strategy was designed and conducted by an experienced librarian using controlled vocabulary with keywords. The electronic search identified 442 publications. After evaluation, six studies from 2015 to 2021 were included, encompassing 201 female patients aged 23 to 75. The diagnosis span post-implantation ranged from 53 to 135.6 months. Studies consistently found bacteria near breast implants in both BIA-ALCL cases and controls, with varied microbial findings. Both BIA-ALCL cases and controls exhibited the presence of specific bacteria, including Pseudomonas aeruginosa, Klebsiella oxytoca, Staphylococcus aureus, and Ralstonia spp., without any statistically significant differences between groups. The use of antiseptic and antimicrobial agents during implant insertion did not demonstrate any impact on reducing or altering the risk of developing BIA-ALCL. Our systematic review reveals that the current evidence is inadequate to link bacterial etiology as a central factor in the development of BIA-ALCL. The limitations in the existing data prevent a complete dismissal of the role of biofilms in its pathogenesis. The observed gap in knowledge underscores the need for more focused and comprehensive research, which should be structured in a multi-faceted approach. Initially, this involves the utilization of sophisticated genomic and proteomic methods. Following this, it is crucial to delve into the study of immunological reactions specifically induced by biofilms. Finally, this research should incorporate extended observational studies, meticulously tracking the evolution of biofilm development and its correlation with the emergence of BIA-ALCL. In light of the inconclusive nature of current findings, further investigation is not only justified but urgently needed to clarify these unresolved issues.
Keywords: Breast; Breast Implants; Proteomics; ženské pohlaví; anaplastický velkobuněčný lymfom; prsní implantáty; Humans; proteomika; Lymphoma, Large-Cell, Anaplastic; Female; prsy; Bacteria; lidé